Interferon-β-1a in relapsing-remitting multiple sclerosis: effect on hypointense lesion volume on T1 weighted images. Issue 5 (1st November 1999) - Gasperini, Claudio; Pozzilli, Carlo; Bastianello, Stefano; Giugni, Elisabetta; Horsfield, Mark A; Koudriavtseva, Tatiana; Galgani, Simona; Paolillo, Andrea; Haggiag, Shalom; Millefiorini, Enrico; Fieschi, Cesare
Abstract : OBJECTIVE: Recently, a strong correlation between the increase in hypointense lesion load on T1 weighted spin echo images, and the increase in disability was reported. Although the effect of interferon-β has been demonstrated both in reducing exacerbation rate, frequency of enhancing lesions, and accumulation of disease burden on T2 weighted images, the impact on the accumulation of hypointense lesions has not yet been evaluated. The aims of the present study were: ( a ) to assess for the first time the effect of interferon-β-1a on T1 weighted MRI hypointense lesion volume; and ( b ) to evaluate the relation between changes on hypointense, hyperintense, and enhancing lesion volume before and during interferon-β-1a treatment in relapsing-remitting multiple sclerosis. METHODS: After a baseline scan and 6 month pretreatment period, 67 patients with relapsing-remitting multiple sclerosis were treated with interferon-β-1a by subcutaneous injection three times a week during a 12 month treatment period. All patients had MRI every month during the 6 month pretreatment period and for the first 9 months of the treatment period. A final MRI was also performed at the end of the 12 month treatment period. RESULTS: There was a significant increase in the mean hyperintense lesion volume during the pretreatment phase (6 months) and a slight decrease during the treatment period (12 months), whereas the hypointense lesion volume increased significantly before treatment and remained substantially stable during treatment. There was a significant correlation between changes in hypointense and hyperintense lesion volume during the observation period, but not during treatment. The monthly mean volume of Gadolinium-DTPA enhancing lesions was significantly higher during the pretreatment than the treatment period, and the enhancing lesion volume correlated with changes of hyperintense and hypointense lesion volumes only during the observation period. CONCLUSION: These data suggest that interferon-β-1a has a stabilising effect on T1 weighted hypointense lesion volume.